2008
DOI: 10.1177/112067210801800410
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Inflammatory Signs Observed in a Cohort of Spanish Patients with Behçet Disease and Ocular Inflammation

Abstract: Women were slightly more affected than men, although the authors found no significant correlation between sex and the clinical variables examined. Apart from one unexpected case of intermediate uveitis, the observations are similar to those reported for other patient series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
(14 reference statements)
2
4
0
3
Order By: Relevance
“…In studies from different parts of the world, panuveitis was reported as the most frequent ocular manifestation in patients with Behçet uveitis. 17,20,23,24 In our patients, the commonest manifestation was retinal vasculitis associated with anterior uveitis and then panuveitis. One-fifth of our patients manifested hypopyon formation at some point in their follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…In studies from different parts of the world, panuveitis was reported as the most frequent ocular manifestation in patients with Behçet uveitis. 17,20,23,24 In our patients, the commonest manifestation was retinal vasculitis associated with anterior uveitis and then panuveitis. One-fifth of our patients manifested hypopyon formation at some point in their follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…Inflammation inside the eye (uveitis and retinitis) occurs in about half of BD patients. Posterior uveitis may be dangerous, and even vision-threatening, because it often causes damage of a crucial part of the eye, the retina [31,34]. Endothelial dysfunction resulting from vascular inflammation is an important factor of thrombosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…A predileção pelo sexo masculino varia com a região em estudo (4)(5)(6)14,(16)(17)(18)(19) . Nesse estudo, encontrou-se predileção pelo sexo feminino (81,3%), descrita também em outros estudos (18)(19)(20) .…”
Section: Discussionunclassified
“…Nesse estudo, encontrou-se predileção pelo sexo feminino (81,3%), descrita também em outros estudos (18)(19)(20) . Verifica-se pior prognóstico para sexo masculino (4,15) , relacionado ao maior ín-dice de panuveíte em homens (5) .…”
Section: Discussionunclassified
See 1 more Smart Citation